The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2013je004480
|View full text |Cite
|
Sign up to set email alerts
|

Global inventory and characterization of pyroclastic deposits on Mercury: New insights into pyroclastic activity from MESSENGER orbital data

Abstract: We present new observations of pyroclastic deposits on the surface of Mercury from data acquired during the orbital phase of the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) mission. The global analysis of pyroclastic deposits brings the total number of such identified features from 40 to 51. Some 90% of pyroclastic deposits are found within impact craters. The locations of most pyroclastic deposits appear to be unrelated to regional smooth plains deposits, except some deposits clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(141 citation statements)
references
References 95 publications
(279 reference statements)
9
132
0
Order By: Relevance
“…In fact, the UV spectral properties of the pyroclastic deposits are clustered and separated from Mercury's background. This has been already shown in previous studies [ Goudge et al , ; Izenberg et al , ] for different pyroclastic deposits. However, it is important to note that all the deposits analyzed in this study and within the same basin are separated from the average surface, supporting the fact that they should indeed be pyroclastic in origin.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In fact, the UV spectral properties of the pyroclastic deposits are clustered and separated from Mercury's background. This has been already shown in previous studies [ Goudge et al , ; Izenberg et al , ] for different pyroclastic deposits. However, it is important to note that all the deposits analyzed in this study and within the same basin are separated from the average surface, supporting the fact that they should indeed be pyroclastic in origin.…”
Section: Resultssupporting
confidence: 85%
“…The figure compiles the candidates from Kerber et al [] and Thomas et al []. The red dots correspond to candidates identified by Thomas et al [], the yellow dots candidates identified by Kerber et al [, ] only, and the blue dot is the candidate analyzed by Goudge et al [] that has not been identified by Thomas et al []. Candidates 13, 21, and 38, although marked in red, have been also analyzed by Goudge et al [].…”
Section: Mercury's Volcanismmentioning
confidence: 99%
“…Since then more than 50 examples have been cataloged (Kerber et al, 2011;Goudge et al, 2014). The deposits are generally higher in reflectance than their surroundings and have an overall spectral slope in the visible to NIR that is steeper (''redder'') than that of the average spectrum for Mercury's surface Murchie et al, 2008;Blewett et al, 2009).…”
Section: Pyroclastic Depositmentioning
confidence: 99%
“…Of particular interest for Mercury are hollows (Blewett et al, , 2013Thomas et al, 2014), pyroclastic deposits (Head et al, 2008;Kerber et al, 2011;Goudge et al, 2014), and a prominent flow of dark impact melt (Klima et al, 2011;D'Incecco et al, 2013). A brief description of the features considered in this report is given in the next section.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to MESSENGER, Mercury's giant core and apparently low ferrous iron surface suggested that materials that accreted and then differentiated to form Mercury were extremely reduced, with an oxygen fugacity 3-5 orders of magnitude below that of the Moon (e.g., McCubbin et al, 2012;Zolotov, 2011). MESSENGER imaging revealed landforms for whose formation volatiles were critical, including pyroclastic vents (e.g., Goudge et al, 2014;Kerber et al, 2011) and hollows ; the latter are extremely fresh features formed by scarp retreat, probably due to loss of volatiles (Blewett et al, , 2016Thomas et al, 2014a). MESSENGER imaging revealed landforms for whose formation volatiles were critical, including pyroclastic vents (e.g., Goudge et al, 2014;Kerber et al, 2011) and hollows ; the latter are extremely fresh features formed by scarp retreat, probably due to loss of volatiles (Blewett et al, , 2016Thomas et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%